The Rare Book Collection of the Library of the Italian National Institute of Health: from the past to the present (Journal of EAHIL, 2023)
The Library of the Istituto Superiore di Sanità (ISS), the Italian National Institute of Health, is the main library for public health and biomedical research in Italy and holds a small but valuable special collection of ancient books. Known as the Rare Book Collection, this fund consists of over 1200 scientific printed volumes published between the XVI and the XIX century. The purpose of this paper is to illustrate the challenges and the process undertaken by the Library to share and digitalize this Collection.